The Effect of Motor Games and Music on Autistic Children's Attention The distraction of attention is one of the major symptoms of children with autism - Ali, Suha (Journal of Physical Education, 2016)
Some autistic children suffer from attention difficulties towards certain things while paying a lot of attention to other sounding things a matter that affect the learning of these children. The aim of the research is to prepare a motor game program for autistic children using music. The researcher used the experimental method. The subjects were (12); (2) for pilot study, and (10) for the main experiment. The subjects were divided into two equal groups; music was applied on one group and motor games were applied on the other group. The researcher concluded that the motor games were better that music. Finally she recommended using both motor games and music on daily bases with autistic children.